Controls on Oxygen Variability and Depletion in the Patuxent River Estuary - Allison Dreiss; Amir Reza Azarnivand; Anna Hildebrand; Seyedeh Fardis Pourreza Ahmadi; Syeda Sadia Ali; Veronica Malabanan Lucchese; Qian Zhang; Laura L. Lapham; Ryan J. Woodland; Lora Harris; Jeremy M. Testa (Estuaries and Coasts, 2024)
Oxygen depletion in coastal waters is increasing globally due primarily to eutrophication and warming. Hypoxia responses to nutrient loading and climate change have been extensively studied in large systems like the Chesapeake Bay and the Baltic Sea, while fewer studies have investigated smaller, shallower hypoxic zones. Thus, an improved understanding of the interactions of eutrophication and warming on hypoxia expansion (or reduction) in the wide variety of different estuarine environments is needed. We examined interannual controls on oxygen depletion in the Patuxent River estuary, a eutrophic sub-estuary of Chesapeake Bay where seasonal hypoxia develops annually. We conducted a spatial and temporal analysis of dissolved oxygen (DO) trends, timing, and several metrics of depletion over a long-term record (1985–2021). We found an internally generated hypoxic zone that initiates in the middle estuary, spreading upstream and downstream as the summer progresses, and that hypoxic volume days (HVD) have been increasing (0.11 per year, p = 0.03) over the record despite reduced watershed nitrogen loads and stable phosphorus loads. River flow and temperature have been increasing and are major drivers of increased HVD, with river flow explaining 40% of the interannual variation in HVD (temperature has increased 0.03 and 0.06 °C per year in summer and fall, respectively). Apparent oxygen utilization (AOU) is increasing in bottom waters in the fall, consistent with increasing trends of both water temperature and stratification strength. HVD was negatively related ( r 2 = 0.34, slope = −0.59*HVD) to the biomass of benthic invertebrates in the middle region of the estuary, suggesting that benthic forage for higher trophic levels will be limited by sustained hypoxia. These results indicate that current and future climate variability plays an important role in regulating oxygen depletion in the Patuxent River estuary, which reinforces the need to factor climate change into strategies for the restoration and management of estuaries.

Fermentation and Anaerobic Oxidation of Organic Carbon in the Oxygen Minimum Zone of the Upwelling Ecosystem Off Concepción, in Central Chile - Benjamín M. Srain; Marcus Sobarzo; Giovanni Daneri; Humberto E. González; Giovanni Testa; Laura Farías; Alex Schwarz; Norma Pérez; Silvio Pantoja-Gutiérrez (Frontiers in Marine Science, 2020)

Acute flaccid paralysis due to Echovirus 30 in an immunosuppressed transplant recipient - Eleonora Mauri; Antonio Mastrangelo; Sara Testa; Laura Pellegrinelli; Elena Pariani; Sandro Binda; Fabio Triulzi; Sergio Barbieri; Cristina Bana; Giovanni Montini; Robertino Dilena (Journal of NeuroVirology, 2020)

Temporal Variability in Net Primary Production in an Upwelling Area off Central Chile (36°S) - Giovanni Testa; Italo Masotti; Laura Farías (Frontiers in Marine Science, 2018)

Combined Cerebellar Proton MR Spectroscopy and DWI Study of Patients with Friedreich’s Ataxia - Laura Ludovica Gramegna; Caterina Tonon; David Neil Manners; Antonella Pini; Rita Rinaldi; Stefano Zanigni; Claudio Bianchini; Stefania Evangelisti; Filippo Fortuna; Valerio Carelli; Claudia Testa; Raffaele Lodi (The Cerebellum, 2017)

Biodiversity, evolution and adaptation of fungi in extreme environments - Laura Selbmann; Eleonora Egidi; Daniela Isola; Silvano Onofri; Laura Zucconi; G. Sybren de Hoog; Selene Chinaglia; Laura Testa; Solveig Tosi; Alma Balestrazzi; Angela Lantieri; Riccardo Compagno; et al. (Plant Biosystems, 2013)

Constitutive over-expression of two wheat pathogenesis-related genes enhances resistance of tobacco plants to Phytophthora nicotianae - Floriana Fiocchetti; Rosalinda D’Amore; Monica De Palma; Laura Bertini; Carla Caruso; Carlo Caporale; Antonino Testa; Gennaro Cristinzio; Francesco Saccardo; Marina Tucci (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)